The impact of pharmacist-led antimicrobial stewardship program on antibiotic use in a county-level tertiary general hospital in China: A retrospective study using difference-in-differences design - Ying Wang; Ying Wang; Chongchong Zhou; Chengying Liu; Shuanghai Liu; Xiaoliang Liu; Xin Li; Xin Li; Xin Li (Frontiers Media S.A., 2022)
BackgroundInappropriate use of antibiotics has become a major driver for the spread of antimicrobial resistance globally, particularly common in China. Antimicrobial stewardship programs are effective in optimizing antimicrobial use and decreasing the emergence of multi-drug-resistant organisms, and the pharmacist has performed a leading role in this program.ObjectiveTo evaluate the impact of antimicrobial stewardship programs driven by pharmacists on antibiotic consumption and costs and the appropriateness of antibiotic use.MethodsA single-center retrospective quasi-experimental design was conducted in two independent hepatobiliary surgery wards and two independent respiratory wards in a county-level tertiary general hospital in Jiangsu, China. Each intervention group was served with antimicrobial stewardship programs with prescriptions audit and feedback, antibiotics restriction, education, and training. The propensity score matching method was employed to balance confounding variables between the intervention group and control group, and a difference-in-differences analysis was used to evaluate the impact of antimicrobial stewardship programs. The primary outcome was measured by scores of rationality evaluation of antibiotics.ResultsThe DID results demonstrated that the implementation of the antimicrobial stewardship programs was associated with a reduction in the average length of hospital stay (coefficient = −3.234, p = 0.006), DDDs per patient (coefficient = −2.352, p = 0.047), and hospitalization costs (coefficient = −7745.818, p = 0.005) in the hepatobiliary surgery ward, while it was associated with a decrease in DDDs per patient (coefficient = −3.948, p = 0.029), defined daily doses per patient day (coefficient = −0.215, p = 0.048), and antibiotic costs (coefficient = −935.087, p = 0.014) in the respiratory ward. The program was also associated with a decrease in rationality evaluation scores (p < 0.001) in two wards.ConclusionThe result reveals that the implementation of the antimicrobial stewardship programs is effective in reducing the length of hospital stay, decreasing antibiotics consumption and costs, and improving the appropriateness of antimicrobial use such as decreasing irrational use of cephalosporins, reducing combinations, and improving timely conversion. However, great attention ought to be paid to the improper use of broad-spectrum antibiotics. The government is responsible for providing sustainable formal education for pharmacists, and more funding and staff support to promote antimicrobial stewardship programs.